Ural Region’s Contribution to Reconstruction of Belarus’s Economy in 1944–1950s - V. V. Zapariy; E. V. Zaytseva (Научный диалог)
This study investigates the role of one of the most powerful regions of the USSR — the Ural — in assisting the restoration and development of the Byelorussian SSR during the final years of World War II and the early postwar period. The research draws on materials from Russian and Belarusian archives. It demonstrates that during this time, the BSSR undertook significant efforts to rehabilitate its economy. The restoration of industry, transportation, agriculture, and other sectors is highlighted. The study emphasizes that substantial support was provided by the republics of the Soviet Union in this endeavor. The novelty of this research lies in the introduction of previously unexamined archival materials from Russian and Belarusian sources, which reveal that Ural enterprises supplied metals, machinery, equipment, timber, raw materials, and other necessities for industrial production. Furthermore, Belarusian specialists received training at Ural enterprises and educational institutions. The authors conclude that the Ural region played a crucial role not only in the reconstruction of the war-torn economy of the republic but also in its subsequent development through the establishment of heavy industry, machine engineering, energy production, and road construction. The mechanisms by which directive bodies from the Ural regions and the Grodno region implemented these decisions are also explored.